Differential patterns of gene expression associated with metastasis in colon cancer - Parle-McDermott, Anne (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2000)
Metastatic spread is the main cause of colon cancer related death and therefore a greater understanding of this process is a prerequisite for improved treatment. The acquisition of metastatic properties confers tumour cells with the ability to leave the primary tumour, invade the circulatory system, survive transport and establish at distant sites. This process must involve the coordinate induction and repression of a range of genes involved in processes such as angiogenesis, proteolysis and growth- independence. Efforts to reach a greater understanding of tumour metastasis has involved analysis of gene expression patterns in tumours with different invasive potentials. However, the majority of studies have focused on the comparison of normal and tumour tissue and an analysis of late stage tumourigenesis, i.e. comparison of primary and metastatic tumours, has not been carried out extensively.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin